PENGARUH MODEL PEMBELAJARAN SINEKTIK TERHADAP KEMAMPUAN MENULIS PUISI BEBAS DAN KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Aprinawati, Iis (2014)
This research was motivated due to the lacking ability of writing free poetry and creative thinking in elementary school. Learning literature in primary schools is very important, especially learning to write a free poetry. By learning to write poetry, the students can explore their potentials and develop their creativity. This study was aimed to determine the effect of using the syntactic learning model towards the ability in writing free poetry and the ability in thinking creatively. The research method used was a quasi experiment. Subjects in this study were fifth grade students of SD Negeri 34 Bandung Soka. The instrument used in this study was a test description (students' poetry writing) to test the ability in writing free poetry and creative thinking ability before and after the given treatment. The treatment given to the experimental class was a syntactic learning model, while the control class was treated with direct learning. Data analysis was performed by quantitative and qualitative statistical analysis through the average different techniques test with significance level α = 0.05. The results of the study showed that the experimental class using syntactic models affects the ability of the student in writing free poetry which can be seen from the mean difference of the experimental class that used syntactic approach and control class that used direct learning. However, the syntactic learning model did not affect significantly the creative thinking ability. It can be seen that there is no difference between the experimental class and the control class.